Consumption of a high-fat diet alters transcriptional rhythmicity in liver from pubertal mice - Yan, Lin; Sundaram, Sneha; Rust, Bret M.; Palmer, Daniel G.; Johnson, LuAnn K.; Zeng, Huawei (Frontiers in Nutrition, 2023)
Childhood obesity is associated with adulthood obesity, which is a risk factor for chronic diseases in adulthood. Obesity, as an environmental cue, alters circadian rhythms. The hypothesis of this study was that consumption of a high-fat diet alters metabolic rhythms in pubertal mice. Weanling female C57BL/6NHsd mice were fed a standard AIN93G diet or a high-fat diet (HFD) for three weeks. Livers were collected from six-week-old mice every four hours over a period of 48 hours for transcriptome analysis. The HFD altered rhythmicity of differentially rhythmic transcripts in liver. Specifically, the HFD elevated expression of circadian genes Clock, Per1, and Cry1 and genes encoding lipid metabolism Fads1 and Fads2, while decreased expression of circadian genes Bmal1 and Per2 and lipid metabolism genes Acaca, Fasn, and Scd1. Hierarchical clustering analysis of differential expression genes showed that the HFD-mediated metabolic disturbance was most active in the dark phase, ranging from Zeitgeber time16 to 20. The Kyoto Encyclopedia of Genes and Genomes enrichment analysis of differentially expressed genes showed that the HFD upregulated signaling pathways related to fatty acid and lipid metabolism, steroid and steroid hormone biosynthesis, amino acid metabolism and protein processing in the endoplasmic reticulum, glutathione metabolism, and ascorbate and aldarate metabolism in the dark phase. Downregulations included MAPK pathway, lipolysis in adipocytes, Ras and Rap1 pathways, and pathways related to focal adhesion, cell adhesion molecules, and extracellular matrix-receptor interaction. In summary, the HFD altered metabolic rhythms in pubertal mice with the greatest alterations in the dark phase. These alterations may disrupt the metabolic homeostasis in puberty and lead to metabolic disorders.